Enhancing Arabic Speaking Proficiency: The Impact of Dialogue Method - Firdaus, Fadhilah Annisa; Ammar , Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the efficacy of the dialogue method in improving students' Arabic speaking skills. Employing a quantitative research approach with a pre-test – post-test control group design, the analysis includes normality tests to ascertain data distribution. The paired sample t test and Ngain test are applied to assess the method's influence on speaking proficiency and quantify its impact. The findings reveal a statistically significant effect of the dialogue method on speaking skills (p < 0.001), with a substantial influence magnitude of 0.4091, categorized as medium. This research underscores the potential of the dialogue method as an effective pedagogical tool for enhancing oral Arabic proficiency, offering valuable insights for language educators worldwide. Highlight: This study assesses the effectiveness of the dialogue method in improving Arabic speaking proficiency. Utilizing quantitative research with a control group design, the analysis includes rigorous tests for data distribution. The findings demonstrate a significant impact of the dialogue method, highlighting its potential as a valuable pedagogical tool for language educators worldwide. Keyword: Dialogue Method, Arabic Speaking Skills, Pedagogical Efficacy, Language Education, Quantitative Research